Predictive Value of Delta-Radiomics Texture Features in 0.35 Tesla Magnetic Resonance Setup Images Acquired During Stereotactic Ablative Radiotherapy of Pancreatic Cancer - Simpson, Garrett; Jin, William; Spieler, Benjamin; Portelance, Lorraine; Mellon, Eric; Kwon, Deukwoo; Ford, John C.; Dogan, Nesrin (Frontiers in Oncology, 2022)
Purpose: The purpose of this work is to explore delta-radiomics texture features for predicting response using set up images of pancreas patients treated with magnetic resonance image guided (MRI-guided) stereotactic ablative radiotherapy (SBRT). Methods: The total biological effective dose (BED) was calculated for 30 patients treated with MRI-guided SBRT that delivered physical doses of 30 to 60 Gy in 3 to 5 fractions. Texture features were then binned into groups based upon BED per fraction by dividing BED by the number of fractions. Delta-radiomics texture features were calculated after delivery of 20 Gy BED (BED20 features) and 40 Gy BED (BED40 features). A random forest (RF) model was constructed using BED20 and then BED40 features to predict binary outcome. During model training the Gini Index, a measure of a variable’s importance for accurate prediction, was calculated for all features and the two features ranked highest selected for internal validation. The two features selected from each bin were used in a bootstrapped logistic regression model to predict response and performance quantified using the area under the receiver operating characteristic curve (AUC). This process was an internal validation analysis. Results: After RF model training, the Gini Index was highest for GLCM Sum Average and NGTDM Busyness for BED20 features and GLSZM Large Zones Low Gray Level Emphasis and GRLRM Run Percentage was selected from the BED40-based features. The mean AUC obtained using the two BED20 features was AUC = 0.845 with the 2.5 percentile and 97.5 percentile values ranging from [0.794 – 0.856]. Internal validation of the BED40 delta-radiomics features resulted in a mean AUC = 0.567 with a 2.5 to 97.5 percentile range of [0.502 – 0.675]. Conclusion: Early changes in treatment quantified with the BED20 delta-radiomics texture features in low field images acquired during MRI-guided SBRT demonstrated better performance in internal validation than features calculated later in treatment. Further analysis of delta-radiomics texture analysis in low field MRI is warranted.